Reality TV shows and empathy in the EFL classroom - LASA ÁLVAREZ, BEGOÑA (Glottodidactica, 2017)
The aim of this study is to explore the extent to which reality TV shows, such as the X Factor, can be effective and emotionally engaging resources in the EFL classroom, particularly for teenagers. Such TV formats, especially the sections in which contestants narrate their personal experiences, have the potential to engage viewers in a powerfully emotional way. Similarly, when used as teaching resources, these first-person discourses are capable of challenging students' empathy very directly, triggering emotionally charged responses to the expressions of others. Thus, under examination here will be the potential value in language teaching and learning of reality TV talent shows and the empathy they produce in students.